2017
DOI: 10.1371/journal.pone.0173173
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of anemia among pregnant mothers attending antenatal care in Dessie town health facilities, northern central Ethiopia, unmatched case -control study

Abstract: IntroductionAnemia affects around 38.2% and 22% of pregnant women at a global and national level respectively. In developing countries, women start pregnancy with already depleted body stores of iron and other vitamins with significant variation of anemia within and between regions.ObjectiveTo identify the determinants of anemia among pregnant mothers attending antenatal care in Dessie town health facilities, northern central Ethiopia.MethodsA health facility based unmatched case control study was conducted am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
36
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 13 publications
12
36
2
2
Order By: Relevance
“…These findings are similar to findings from several other studies on risk factors for anaemia in pregnancy in other settings. [30,31,[39][40][41][42][43] This underscores the need to pay special attention to women of lower parity, who sometimes have poor spacing between births, with the aim of educating them on anaemia prevention measures, especially during pregnancy. The need to educate pregnant women, especially those in the rural areas on the importance of early booking and booking in certified health facilities is also of utmost importance.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to findings from several other studies on risk factors for anaemia in pregnancy in other settings. [30,31,[39][40][41][42][43] This underscores the need to pay special attention to women of lower parity, who sometimes have poor spacing between births, with the aim of educating them on anaemia prevention measures, especially during pregnancy. The need to educate pregnant women, especially those in the rural areas on the importance of early booking and booking in certified health facilities is also of utmost importance.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia has both short- and long-term consequences such as preterm, low birth weight, morbidity and mortality 1,2,3,4 . In 2016, World Health Organization (WHO) estimated that anemia affected 38.2% of pregnant women globally, with the highest prevalence in South-East Asia (48.7%) and Africa (46.3%) 5,6 . Anemia affects about 1.62 billion people, 56 million of whom are pregnant women 5 .…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries, pregnant women often start gestation with depleted or low body iron stores, making them especially vulnerable to iron deficiency anemia 6,10,11,12 . Hb concentration declines during pregnancy, partly because of expanded plasma volume compared to red cell mass 10,13 .…”
Section: Introductionmentioning
confidence: 99%
“…The authors noted that the risk of anemia was 6.78 times more in women who had HIV infection compared to those who had no HIV infection. 8 Mekonnen FA et al found that the prevalence of anemia was 10%. 64.3% were found to have mild anemia.…”
Section: Discussionmentioning
confidence: 99%